2009
DOI: 10.1002/jcb.22393
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases A and C and phosphatidylinositol 3 kinase regulate glycogen synthase kinase‐3A serine 21 phosphorylation in boar spermatozoa

Abstract: The cAMP-dependent protein kinase (PKA), protein kinase C (PKC) and phosphatidylinositol 3-kinase (PI3K) pathways control most relevant functions in male germ cells including motility. Recently we demonstrated that phosphorylation state of glycogen synthase kinase-3alpha (GSK3A) is also a key event in the control of boar spermatozoa motility. However, the upstream regulators of GSK3A serine phosphorylation (inhibition) in male germ cells remain largely unknown. This work investigates the involvement of PKA, PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
5
25
0
Order By: Relevance
“…However, this effect was not observed in calcium depleted media. This result suggests that PKA lies upstream of PKC in the boar sperm intracellular pathway, supporting a previous work by us (Bragado et al, 2010), and that it is also involved in lipid organization of the plasma membrane. Interestingly, PKC-stimulated membrane fluidity is higher when calcium is present in the medium, showing that the canonical calcium pathway involved in membrane fluidity is also present and functional (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, this effect was not observed in calcium depleted media. This result suggests that PKA lies upstream of PKC in the boar sperm intracellular pathway, supporting a previous work by us (Bragado et al, 2010), and that it is also involved in lipid organization of the plasma membrane. Interestingly, PKC-stimulated membrane fluidity is higher when calcium is present in the medium, showing that the canonical calcium pathway involved in membrane fluidity is also present and functional (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, membrane acrosome integrity is also affected by those components (Purohit et al, 1999;Visconti et al, 1999;Breitbart, 2002;Ickowicz et al, 2012), but enhanced in each medium by PMA treatment. As an interconnection between PKA and PKC in boar sperm signaling pathway has been suggested (Bragado et al, 2010), we also studied the effect of H89, a PKA inhibitor, on plasma membrane fluidity. Noteworthy, the obtained results suggest the presence of a PKA-dependent and calcium-independent mechanism/pathway involved in the control of the fluidity of boar sperm plasma membrane (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For GSK3a, it was demonstrated that phosphorylation of Ser21 by PKA can lead to its enzymatic inhibition. 40 With regard to Ca 21 signaling, pleckstrin phosphorylation (Thr123: ↑30 5nM ; Ser117: ↑60 5nM , a major PKC target in platelets 41 ) is regulated, whereas CalDAG-GEF1 phosphorylation is regulated at Ser576 (↑10 2/5nM ) and potentially PKA phosphorylated at Ser116 and Ser117 (both: ↑10 2/5nM ) as well as Ser587 (↑30/10 2/5nM ), which is in accordance with our own recent data 20 demonstrating that phosphorylation of CalDAG-GEF1 inhibits Rap1b activation in human platelets. Moreover, cPLA2 phosphorylation is upregulated at Ser727 (↑30 2/5nM ).…”
Section: Kinases and Phosphatases Involved In Platelet Inhibitionmentioning
confidence: 99%
“…CT99021 at 1 mM was shown to reduce GSK3b activity to 1% in an in vitro assay in which the inhibitor was shown to be highly specific [32]. H-89 at 10 mM was used to activate GSK3, as it is a robust activator of GSK3 whose inclusion in culture medium has been shown to prevent or inhibit the phosphorylation of GSK3 (which would inactivate GSK3) in embryonic kidney cells at 10 mM [31,50], muscle cells at 50 mM [51], spermatozoa at 100 mM [52], and glioma cells at 10 mM [53]. Pifithrin-a was used to inhibit p53 at 30 mM [38], as it has been established as an effective inhibitor of p53 that blocks the activation of p53 responsive LacZ in ConA cells, and inhibits p53-mediated apoptosis at 10-20 mM [54].…”
Section: Insulin and Inhibitorsmentioning
confidence: 99%